Impact of digital transformation on employee engagement at Ceylon Electricity Board in the Northern Province of Sri Lanka - Thileepan, J.; Raveendran, T. (Rajarata University of Sri Lanka, 2022)
Most of the organizations in the present complex business era have understood the dynamic environment of business and focus on how information technologies are creating digital transformation. To meet the challenges of digital transformation, business firms require greatly encouraged, motivated, and engaged employees at all the level of business processes. In this study, an effort was made to examine the digital transformation and its impact on employee engagement. A sample of 273 staff were selected from Ceylon Electricity Board in Northern Province of Sri Lanka using stratified random sampling method. In this study, an explanatory research design was employed in a cross-sectional time horizon and a survey method was used. The variables were measured using standard questionnaires. Correlation and regression analyses were performed to identify the association between the variables and ANOVA and Independent sample t-test were performed to compare means. The study revealed that the dimensions of digital transformation namely customer service, operational efficiency and business modelling positively impact employee engagement. The research provides useful understandings for administrators to realize the connection among digital transformation and employee engagement and how far each of the dimensions of digital transformation contributes to increase employee engagement. Based on the results, recommendations are made to enhance the employee engagement in the workplace.
Keywords: Business modeling; Customer service; Digital transformation; Employee engagement; Operational efficiency